1994
DOI: 10.1007/bf00194397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluconazole on theophylline disposition in humans

Abstract: The effect of fluconazole, an antimycotic that inhibits cytochrome P-450-mediated drug metabolism, on theophylline kinetics and the production of its metabolites were compared with those of enoxacin in 5 healthy subjects. All subjects received a single oral dose of 240 mg theophylline (aminophylline, 300 mg) after they had been given oral fluconazole 100 mg every 12 h or enoxacin 200 mg every 8 h for three consecutive days. Pretreatment with enoxacin decreased the total clearance (CLT) and elimination rate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…Fluvoxamine is known to inhibit this enzyme potently in vitro and in vivo; however, to explain the Ͼ100-fold interaction CYP1A2 would need to be virtually the only enzyme involved in ramelteon clearance. This is clearly not the case because coadministration of ramelteon with ketoconazole and fluconazole both yield DDI (1.82-and 2.36-fold increases, respectively), whereas neither of these drugs is known to affect CYP1A2-cleared drugs (Naline et al, 1988;Konishi et al, 1994). However, in the present study it was shown that CYP2C19 and CYP3A4 also contribute to ramelteon metabolism.…”
Section: Discussioncontrasting
confidence: 64%
“…Fluvoxamine is known to inhibit this enzyme potently in vitro and in vivo; however, to explain the Ͼ100-fold interaction CYP1A2 would need to be virtually the only enzyme involved in ramelteon clearance. This is clearly not the case because coadministration of ramelteon with ketoconazole and fluconazole both yield DDI (1.82-and 2.36-fold increases, respectively), whereas neither of these drugs is known to affect CYP1A2-cleared drugs (Naline et al, 1988;Konishi et al, 1994). However, in the present study it was shown that CYP2C19 and CYP3A4 also contribute to ramelteon metabolism.…”
Section: Discussioncontrasting
confidence: 64%
“…It appears that fluconazole also does not appreciably inhibit CYP1A2 on the basis of the results of interaction studies with theophylline and warfarin, which are substrates for this isoenzyme. When taken with fluconazole, theophylline clearance was reduced only 16% and the formation clearance of theophylline metabolites was decreased by about 15% (22). The area under the prothrombin activity curve for warfarin was just 7% higher when this compound was taken with fluconazole (23).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, amiodarone is an inhibitor of CYP1A2, whose substrate is theophylline [57]. The use of fluconazole, on the other hand, can be associated with the decreased clearance of theophylline by about 13-16% [58,59]. One study in which theophylline was used with pentoxyllin has demonstrated an increase in theophylline concentration by 30% on average (ranging from an increase by 95% to a decrease by 13%) [60].…”
Section: Theophyllinementioning
confidence: 99%